2012
DOI: 10.1017/s0033822200047391
|View full text |Cite
|
Sign up to set email alerts
|

14C Chronology of Burial Grounds of the Andronovo Period (Middle Bronze Age) in Baraba Forest Steppe, Western Siberia

Abstract: ABSTRACT. This paper focuses on the chronology of Middle Bronze Age complexes in the Baraba forest steppe (western Siberia). Three sites were radiocarbon dated, Stary Tartas 4, Sopka 2, and Tartas 1. The Late Krotovo culture was dated to the 18-19th centuries BC, the Andronovo complex (Fedorovo stage) to the 15-18th centuries BC, and the Mixed Andronovo complex dated to the 15-17th centuries BC. These values are some 300-500 yr older than previously thought, and the new results are consistent with 14 C dates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The core of the site is Bronze Age burials, the majority of which date to the first part of the 2 nd mil. cal BC (Molodin et al 2012). Burial 487 contained bronze celt ( Figure 2, item 7; Molodin et al 2011) and the remains of 20-25 years old woman, positioned similar to burials of Sopka 2/4C on the back with knees bent up.…”
Section: Archaeological Sitesmentioning
confidence: 97%
See 1 more Smart Citation
“…The core of the site is Bronze Age burials, the majority of which date to the first part of the 2 nd mil. cal BC (Molodin et al 2012). Burial 487 contained bronze celt ( Figure 2, item 7; Molodin et al 2011) and the remains of 20-25 years old woman, positioned similar to burials of Sopka 2/4C on the back with knees bent up.…”
Section: Archaeological Sitesmentioning
confidence: 97%
“…The necropoleis of Sopka 2/4B and Sopka 2/4C (55°37.3′N, 76°44.5′E), Tartas 1 (55°38.1′N, 76°44.1′E), and Preobrazhenka 6 (55°30.1′N, 77°00.9′E) are located in the central part of the Baraba forest-steppe (Molodin 1985, 2001, 2012; Molodin et al 2003, 2007, 2011, 2015; Marchenko et al 2015). Sopka 2/4B represents a group of graves of the Krotovo Culture within the Sopka 2 necropolis consisting of more than 600 Neolithic to Medieval burials in total (Molodin 1985, 2001, 2012). Burial 427 contained the casting mold for the ST type bronze spear.…”
Section: Archaeological Sitesmentioning
confidence: 99%
“…It is clear that all archaeological complexes mentioned above are relatively young, not older than ca 6000e4000 BP (Molodin, 2001;Molodin et al, 2012;Kuzmin, 2014). Based on available 14 C dates of giant deer in Siberia up to ca 6900 BP (Stuart et al, 2004), it has been suggested that at these sites its age could be even younger (Vasiliev et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The use of radiocarbon dating is a crucial and inherent aspect of modern archaeological research. A growing body of 14 C dates is being released for a number of Eurasian Steppe regions, including southern Siberia (Alekseev et al 2001; Svyatko et al 2009; Kiryushin and Tishkin 2009), Baraba forest-steppe (Molodin et al 2012), southern Ural Mountains (Hanks et al 2007), North Caucasus (Higham et al 2010; Hollund et al 2010), North Caspian steppes (Shishlina et al 2009, 2012, 2014), Dnieper Basin (Lillie 1998; Alekseev et al 2001; Lillie et al 2009), and the steppes in general (Chernykh et al 2004). However, in the very heart of the Eurasian Steppe region, Kazakhstan, archaeological research using 14 C dating is only in its formative stage.…”
Section: Introductionmentioning
confidence: 99%